Teachers’ Feedback and Professional Growth in Teacher Education: Implications for Feedback Literacy - Alice Rachmahanani Putri; Mateus Yumarnamto (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2024)
Teachers’ feedback is important as it provides a starting point for improvement. This study explored teachers’ feedback in the contexts of In-Service Teacher Professional Education Program (Pendidikan Profesi guru Dalam Jabatan/PPG-DalJab). The participants were eight teachers joining the program in 2021. The leading question for the inquiry is related to the feedback the teachers used and how the use of different feedback reflected their feedback literacy. The data were collected from the participants in the form of video recordings of participating teachers’ classes, reflective discussions with the mentor, and documents related to their teaching practice. The data were analyzed for their emerging themes related to feedback given by the teachers during their teachings. This process involved, data coding, identification, and classification of the feedback. The findings indicate that the dominant types of feedback used by the teachers were evaluative feedback, interactional feedback, motivational feedback and corrective feedback. Considering the findings, it is important that English teachers should be aware about their feedback in the classroom for more effective teaching. More importantly, the findings also implied the importance of feedback literacy for teacher professional growth.